29‐4: Invited Paper: Novel High Impedance Driving of Zenithal Bistable LCDs. Issue 1 (28th June 2022) - Beldon, Stephen M.; Shi, Quanshui; Pfeiffer, Matthias; Bryan-Brown, Guy
Abstract : The addressing of passive matrix LCDs is well known, with predefined voltages being applied to both rows and columns during an update. In this paper we present a novel method of driving a Zenithal Bistable LCD, applying a high impedance state to inactive rows and/or columns. Significant improvements in power consumption are demonstrated.